Integrate the product of sums!

Calculus Level 5

I = 0 ( x x 3 2 + x 5 2 4 x 7 2 4 6 + ) ( 1 + x 2 2 2 + x 4 2 2 4 2 + x 6 2 2 4 2 6 2 + ) d x \displaystyle I = \int_0^\infty {\left(x - \frac{x^3}{2} + \frac{x^5}{2 \cdot 4} - \frac{x^7}{2 \cdot 4 \cdot 6} + \cdots \right) \left(1 + \frac{x^2}{2^2} + \frac{x^4}{2^2 \cdot 4^2} + \frac{x^6}{2^2 \cdot 4^2 \cdot 6^2} + \cdots \right) \, dx}

The integral I I above has a closed form. Find the value of this closed form.

Submit your answer as I 2 I^2 to 2 decimal places.


The answer is 2.72.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Let I = 0 f ( x ) g ( x ) d x \displaystyle I=\int_{0}^{\infty} f(x)g(x)dx

f ( x ) = n = 1 ( 1 ) n 1 x 2 n 1 k = 1 n 1 2 k = x n = 1 ( 1 ) n 1 x 2 ( n 1 ) 2 n 1 ( n 1 ) ! = x e x 2 2 \displaystyle \color{#D61F06}{f(x)} = \color{#3D99F6}{\sum_{n=1}^{\infty} (-1)^{n-1}\frac{x^{2n-1}}{\prod_{k=1}^{n-1}2k} = x\sum_{n=1}^{\infty}(-1)^{n-1} \frac{x^{2(n-1)}}{2^{n-1}(n-1)!} = xe^{-\frac{x^2}{2}}}

g ( x ) = n = 0 x 2 n 4 n ( n ! ) 2 = I 0 ( x ) \displaystyle \color{#D61F06}{g(x)} = \color{#3D99F6}{\sum_{n=0}^{\infty} \frac{x^{2n}}{4^n(n!)^2} = I_0(x)}

Here I n ( x ) I_n(x) is the Modified Bessel Function of the First kind , but we'll evaluate the integral step by step without using a standard result of Bessel Functions.

I = 0 f ( x ) g ( x ) d x = n = 0 1 4 n ( n ! ) 2 0 x e x 2 2 x 2 n d x \displaystyle I = \int_{0}^{\infty} f(x)g(x) dx = \sum_{n=0}^{\infty}\frac{1}{4^n(n!)^2} \int_{0}^{\infty}xe^{-\frac{x^2}{2}}x^{2n}dx

So, I = n = 0 1 2 n ( n ! ) 2 0 e t t n d t G a m m a F u n c t i o n = n = 0 Γ ( n + 1 ) 2 n Γ 2 ( n + 1 ) = n = 0 = ( 1 2 ) n n ! = e \displaystyle I = \sum_{n=0}^{\infty}\frac{1}{2^n(n!)^2} \underbrace{\color{#D61F06}{\int_{0}^{\infty} e^{-t}t^{n} dt}}_{Gamma Function} = \sum_{n=0}^{\infty} \frac{\Gamma(n+1)}{2^n\Gamma^2(n+1)} = \sum_{n=0}^{\infty}=\frac{(\frac{1}{2})^n}{n!} = \sqrt{e}

So, I 2 = e \displaystyle I^2 =\boxed{e}

how 4 n 4^n become 2 n 2^n in the denominator ???

Kushal Bose - 4 years, 7 months ago

Use the substitution x 2 2 = t \displaystyle \frac{x^2}{2}=t

Aditya Narayan Sharma - 4 years, 7 months ago

This was Prob A3 on the 1997 William J. Putnam examination.....nice!

tom engelsman - 4 years, 6 months ago

Log in to reply

I see! How was it solved there?

Aditya Narayan Sharma - 4 years, 6 months ago

Nice solution. The only difference between your solution and mine is in the evaluation of f(x). I simply complicated it and used the general form of (2n)!!. But alas, landed on the same result.

Aditya Kumar - 4 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...